Hetero‐Integration of Silicon Nanomembranes with 2D Materials for Bioresorbable, Wireless Neurochemical System. Issue 14 (17th February 2022) - Yang, Seung Min; Shim, Jae Hyung; Cho, Hyun‐U; Jang, Tae‐Min; Ko, Gwan‐Jin; Shim, Jeongeun; Kim, Tae Hee; Zhu, Jia; Park, Sangun; Kim, Yoon Seok; Joung, Su‐Yeon; Choe, Jong Chan; et al.
Abstract: Although neurotransmitters are key substances closely related to evaluating degenerative brain diseases as well as regulating essential functions in the body, many research efforts have not been focused on direct observation of such biochemical messengers, rather on monitoring relatively associated physical, mechanical, and electrophysiological parameters. Here, a bioresorbable silicon‐based neurochemical analyzer incorporated with 2D transition metal dichalcogenides is introduced as a completely implantable brain‐integrated system that can wirelessly monitor time‐dynamic behaviors of dopamine and relevant parameters in a simultaneous mode. An extensive range of examinations of molybdenum/tungsten disulfide (MoS2 /WS2 ) nanosheets and catalytic iron nanoparticles (Fe NPs) highlights the underlying mechanisms of strong chemical and target‐specific responses to the neurotransmitters, along with theoretical modeling tools. Systematic characterizations demonstrate reversible, stable, and long‐term operational performances of the degradable bioelectronics with excellent sensitivity and selectivity over those of non‐dissolvable counterparts. A complete set of in vivo experiments with comparative analysis using carbon‐fiber electrodes illustrates the capability for potential use as a clinically accessible tool to associated neurodegenerative diseases. Abstract : A soft, wireless, and bioresorbable neurochemical system designed to determine various concentrations of neurotransmitters as well as to monitor peripheral physiologies (temperature, pH, electrical activity) in a simultaneous manner is presented. An extensive range of studies covers modifications of nanoscale materials and system‐level electronics, enabling the production of exceptional performance.